Metabolism in the tumour-bone microenvironment - Whitburn, J; Edwards, CM (Springer, 2021)
Purpose of Review For solid tumours such as breast and prostate cancer, and haematological malignancies such as myeloma, bone represents a supportive home, where the cellular crosstalk is known to underlie both tumour growth and survival, and the development of the associated bone disease. The importance of metabolic reprogramming is becoming increasingly recognised, particularly within cancer biology, enabling tumours to adapt to changing environments and pressures. This review will discuss our current understanding of metabolic requirements and adaptations within the tumour-bone microenvironment. Recent Findings The bone provides a unique metabolic microenvironment, home to highly energy-intensive processes such as bone resorption and bone formation, both of which are dysregulated in the presence of cancer. Approaches such as metabolomics demonstrate metabolic plasticity in patients with advanced disease. Metabolic crosstalk between tumour cells and surrounding stroma supports disease pathogenesis. Summary There is increasing evidence for a key role for metabolic reprogramming within the tumour-bone microenvironment to drive disease progression. As such, understanding these metabolic adaptations should reveal new therapeutic targets and approaches.